The People's Health (Newcastle-on-Tyne : North-East District Committee, Communist Party, 1943)
1943-10 1943 1940s 36 pages people realise that the day-to-day ills and diseases from which so many workers suffer, are in many cases directly attributable to the nature of their work. Too few people realise that rheumatism, T.B., dermatitis, as well as ordinary colds and influenza, to which they are subject every winter, are directly responsible to the fact that the factory owner or employer has not provided them with the conditions laid down by Act of Parliament. If this Conference achieves nothing more than the establishment in every factory and industrial undertaking in the North-East of a Workers' Health and Welfare Committee it will have proved of great value to the workers. Material is issued by His Majesty's Stationery Office which gives full particulars of industrial health legislation. But that is only one aspect of this subject and today it is not my privilege to speak at length on it. I am simply here to outline the nature of the Conference. OPENING SPEECH. Dr. T.O. GARLAND, M.D. D.P.H. (Member of British Medical Association's Committee on Industrial Health). The Ministry of Health has just issued its summary report of the health of the country in 1942, and before I get on to the narrower field of industrial health, I just want to call attention to a few of the figures which have been published in the Report. Some of them are extremely striking. There have been a number of records set up in 1942, in spite of the fact that we are in the fourth year of the war. The infantile mortality rate, one of the most sensitive indices of health of infants — the number of infants dying within a year of birth, was 49 per 1,000 — the lowest ever in this country. The death rate amongst children aged 1 year to 5 was down to the lowest pre-war levels and amongst children aged 5 to 15, the death rate was 2 per cent. lower than ever before. The death rate amongst civilian men and women was lower than ever before, and amongst civilian women — in spite of the large group of healthy young women in the Services, the result was 8 per cent. lower than ever before. These are only some of the good things. Some of the bad things are : the alarming rise in the prevalence of venereal diseases. Syphilis has gone up every year of the war by 30, 40 and 30 per cent. and now in 100's on pre-war figures and the number of cases of Gonorrhea 7 or 8 times those of syphilis. T.B. in the first three years of the war showed a steep rise in deaths as well as in incidence. 1942 showed a fall in deaths but a further rise in incidence of 3 per cent. Then there are other black spots — shortage of maternity beds, shortage of staff in hospitals, an epidemic of catarrhal jaundice. 4 15X/2/103/295